(untitled) (Applied Biological Research, 2019)
The present study was conducted on 48 rice genotypes with the aim to assess the genetic relationship between culm strength and its influencing traits in rice. Culm strength of rice has been used as an index of lodging resistance and it was measured as pushing resistance by prostrate tester. Correlation analysis revealed that culm strength is significantly positively correlated with culm diameter, panicle number and culm wall thickness. Principal component analysis revealed that the first four principal components with Eigen value > 1 explained 79.36% cumulative variance. The maximum variation explained by culm strength and its related traits like culm diameter and culm wall thickness which showed positive contribution in all the four components. Distribution of genotypes into four clusters, based on Ward’s minimum variance method, showed that cluster-IV had high mean (261.4 g stem-1) and cluster-II low mean (96.21 g stem-1) values of culm strength. The electron microscopic observations of vascular tissues of lower most elongated internode of four genotypes ‘CR 401’ and ‘Pusa-44’ from cluster-IV and ‘Swarna’ and ‘BPT-5204’ from cluster-II revealed significant variation in vascular tissue and phloem diameter among the tested genotypes. This indicated significant diversity among rice genotypes which can be useful for identifying the QTLs for culm strength and for releasing new cultivar.